2015
DOI: 10.1002/aenm.201501654
|View full text |Cite
|
Sign up to set email alerts
|

Degenerating Plasmonic Modes to Enhance the Performance of Surface Plasmon Resonance for Application in Solar Energy Conversion

Abstract: generation of photoinduced charge carriers which is a fundamental issue in the fi eld of solar energy conversion. [ 2 ] Undoubtedly, this work will provide guidance on how to take full advantages of the SPR effect in applications, such as future designing plasmonic devices in the fi elds of solar energy conversions.This study based on the combining our improved ultrathin alumina membrane (UTAM) technique with atomic layer deposition (ALD) method. [ 17,18 ] As known, SPR property is very sensitive to structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 32 publications
0
47
0
Order By: Relevance
“…Coating Ag with TiO 2 shells, the quadrupole SPR mode of ordered Ag nanoparticles in UV region was degenerated to coincide with dipole mode in visible region through changing the deviations of refractive index between Ag core and outer dielectric TiO 2 shells. This degeneracy of SPR modes greatly promoted the generation of photoinduced charge carriers and enhanced the photocatalytic activity . The plasmon resonance wavelength and line width of plasmonic nanoparticles can also be adjusted through varying the shell thickness and aspect ratio of the bimetallic core–shell nanostructures.…”
Section: Semiconductors In Photoelectrochemistrymentioning
confidence: 99%
“…Coating Ag with TiO 2 shells, the quadrupole SPR mode of ordered Ag nanoparticles in UV region was degenerated to coincide with dipole mode in visible region through changing the deviations of refractive index between Ag core and outer dielectric TiO 2 shells. This degeneracy of SPR modes greatly promoted the generation of photoinduced charge carriers and enhanced the photocatalytic activity . The plasmon resonance wavelength and line width of plasmonic nanoparticles can also be adjusted through varying the shell thickness and aspect ratio of the bimetallic core–shell nanostructures.…”
Section: Semiconductors In Photoelectrochemistrymentioning
confidence: 99%
“…For example, it has been reported that metal nitrides (ZrN and TiN) can be used as alternative to plasmonic metals for vis‐NIR‐responsive photocatalysis . Since plasmonic resonances are closely associated with the material properties, we strongly envisage that new plasmonic materials will definitely bring more degree of freedom for spectral design, thereby resulting in the production of more diverse plasmonic electrodes for PEC water splitting.…”
Section: Outlooks and Future Perspectivesmentioning
confidence: 99%
“…S2 and Table 1, the grain sizes of composite 1-5 were between 3.4 and 11.7 nm. It can be observed that Ag NPs have been obtained with narrow size distributions [20]. This study indicates that the porous structure facilitate the separation of photo-generated electron-hole pairs [52].…”
Section: Characterizationmentioning
confidence: 67%
“…Among various candidates, Ag NPs is one of the most effective sensitizers in photocatalytic H 2 evolution [18,19], due to their relative low cost, facile preparation and high efficiency under near-neutral pH conditions [20,21]. It is also proved that Ag NPs displays strong surface plasmon resonance (SPR) effect even its size decreases to below 10 nm [20,22]. As for their promising light-harvesting and electron transfer properties, Ag NPs have been successfully incorporated with M-complexes and underexplored in photocatalytic applications [11,23].…”
Section: Introductionmentioning
confidence: 99%